2015
DOI: 10.1080/09571264.2015.1031883
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing adaptation outcomes for transformation: climate change in the Australian wine industry

Abstract: As climate change progresses, an increasing number of wine industry enterprises and other resource-based enterprises will need to transform. It is therefore important for research accounts to provide contextual understandings of how transformations are occurring to help inform other stakeholders facing decisions of how, when and even if they might consider transformation. Our work provides an account of how adaptations are currently occurring in the wine industry, focusing on decision-making. Nineteen intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
1
25
1
Order By: Relevance
“…Table 6 describes the ANOVA results representing BM (between mean squares of all groups) and WM (within mean square of a group) and theirstatistics value for each dataset. We observed that the -test statistic exceeds the significance level of crit (0.05) in all cases except healthy voice data and heart rate variability data (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). For example, for US Climate dataset as seen by the ANOVA test, the calculated -test statistic (5.10) is greater than -critical.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…Table 6 describes the ANOVA results representing BM (between mean squares of all groups) and WM (within mean square of a group) and theirstatistics value for each dataset. We observed that the -test statistic exceeds the significance level of crit (0.05) in all cases except healthy voice data and heart rate variability data (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). For example, for US Climate dataset as seen by the ANOVA test, the calculated -test statistic (5.10) is greater than -critical.…”
mentioning
confidence: 95%
“…It is done by grouping the CPR values into three categories as (a) strongly related (CT = 1), (b) moderately related (CT = 0), and (c) weakly related (CT = −1) using (13). CPR values are calculated using (4) along with the number of pairs for which the CPR value has to be calculated using (12).…”
Section: Connectivity Trend Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The latter has been found to impede pro-environmental behavior in certain circumstances (Gifford, 2011) and facilitate it in others (Devine-Wright, 2009;Scannell and Gifford, 2010), and may serve to support incremental strategies but act as a constraint to transformation. Marshall et al (2012Marshall et al ( , 2013 and Marshall and Stokes (2014) found that values of identity and place acted as significant barriers to transformative capacity in the Australian agricultural industry (see also Fleming et al, 2015). Where strong attachment to place exists, individuals are likely to assess transformative change as a threat to place identity and may resist unwanted change (DevineWright, 2009;Anton and Lawrence, 2016).…”
Section: Social and Cultural Barriersmentioning
confidence: 99%